The introduction of the latest technologies and devices in the field of railway transport (Международный научный журнал «Инженер», 2026)
The article covers issues related to the description of modern aspects of improving the efficiency and safetyof train traffic, improving the quality of transport services for passengers and shippers, as well as contributingto the economic development of the region through the implementation of comprehensive modernization atstations and railway sections. The introduction of intelligent monitoring and diagnostic systems for rollingstock is recommended. It has been established that the introduction of automated control systems implies asignificant reduction in the cost of train traffic management. It has been established that the introduction ofintelligent systems for monitoring and diagnosing the condition of the track using sensors and artificialintelligence (AI) is also an important area in the development of track facilities. As a result, the successfuldevelopment of railway transport requires a holistic approach that includes increasing investmentattractiveness, introducing modern technologies, and taking into account the social needs of users.